Pengaruh Pendekatan Kontekstual dalam Motivasi Belajar Siswa Sekolah Menengah Pertama - Sukma Nurmawarni (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
This study has the aim of knowing students' understanding and motivation with the CTL approach. In the learning process is bound to the learning approach so that the learning process can run optimally, fun and full of meaning. In contextual learning students must connect knowledge through material provided by educators and connect with real life. Data collection was carried out by giving questionnaires to students' subjects from SMPN 1 Sukorambi. If you use the CTL method, students' memory will become strong and will not be forgotten. Keywords: students, CTL, meaningful learning.